Better vertebrae remodeling in pediatric spinal eosinophilic granuloma patients treated with kyphoplasty and short-term posterior instrumentation: A minimal two-year follow-up with historical controls - Zheng, Yiming; Zhang, Zhiqiang; Wang, Dahui (Frontiers in Pediatrics, 2022)
Objective To assess the validity and safety of kyphoplasty combined with short-term posterior instrumentation to treat children with vertebrae plana due to eosinophilic granuloma (EG). Patients and Methods Clinical data of EG patients, who received kyphoplasty and short-term instrumentation from March 2019 to March 2020, were retrospectively reviewed. The recovery of diseased vertebrae was assessed and compared with historical case data. Results Nine patients with EG had received kyphoplasty and short-term posterior instrumentation. The mean age at initial treatment was 66.7 months old (range, 28–132 months). The average number of follow-up months was 26.7. (range, 24–30 months).Four and 5 cases presented with thoracic and lumbar vertebral destruction, respectively. Under Garg's classification, 7 and 2 cases were classified as Grade IIA and IIB, respectively. The average diseased vertebral heights at 1-year and 2-year after surgery were significantly higher than the preoperative heights. The average percentages of diseased vertebral heights to references at 1-year and 2-year after surgery were 72.0% and 86.0%, respectively. The average percentage of diseased vertebral heights to the references at 2-year after surgery was significantly higher than that of the historical cases at the same time. No minor or major adverse events were observed. Conclusions Transpedicular balloon kyphoplasty for the direct restoration of vertebrae plana seems feasible and safe in combination with short-term posterior instrumentation. Better short-time vertebrae remodeling was observed 2 years after surgery. Active surgical treatment is suggested for children who have vertebrae plana as a result of EG in order to maintain the ability to recover vertebral height.